Management accounting - Chadwick, Leslie (London : International Thomson Business Press, 1998)
Yhis book is about: An introduction to management accounting; The elements of cost; An introduction to overheads and total absorption costing; Marginal costing and break-even analysis; ...
Keywords: Accounting; Managerial accounting